Determinants of p16/Ki‐67 adequacy and positivity in HPV‐positive women from a screening population. Issue 5 (3rd November 2020) - Benevolo, Maria; Mancuso, Pamela; Allia, Elena; Gustinucci, Daniela; Bulletti, Simonetta; Cesarini, Elena; Carozzi, Francesca Maria; Confortini, Massimo; Bisanzi, Simonetta; Rubino, Teresa; Rollo, Francesca; Marchi, Natalina; et al.
Abstract : Background: The objective of this study was to describe the determinants of adequacy and positivity of the p16/Ki‐67 assay in a human papillomavirus (HPV)‐positive screening population enrolled within the New Technologies for Cervical Cancer 2 (NTCC2) study. Methods: ThinPrep slides were immunostained for p16/Ki‐67; each slide had 3 reports from different laboratories. The authors included population‐related, sampling‐related/staining‐related, and interpretation‐related variables in the analyses. Adequacy and positivity proportions were stratified by variables of interest. Univariate and multivariate logistic models were used to identify determinants of adequacy and positivity. Results: In total, 3100 consecutive HPV‐positive cases were analyzed. Because every slide was interpreted by 3 centers, 9300 reports were obtained, including 905 (9.7%) that were inadequate and 2632 (28.3%) that were positive. The percentage of cases in which all 3 reports were inadequate increased with increasing age of the women and with inadequate cytology. The highest percentage of adequacy in all 3 reports and of cases with all 3 reports positive was observed in specimens from women who had grade ≥2 cervical intraepithelial neoplasia (CIN2+), atypical squamous cells of undetermined significance or more severe (ASC‐US+) cytology, or mRNA positivity. The number of inadequate reports was significantly associated with increasing age, inadequate cytology, mRNA negativity, and scant cellularity. A positive p16/Ki‐67 report was associated with an ASC‐US+ result and with a positive mRNA result in cases both with and without CIN2+ but was associated with an HPV type 16 and/or 18 infection only in CIN2+ cases. The presence of CIN2+ was strongly associated with dual staining positivity. Conclusions: The interpretation of p16/Ki‐67 results may be influenced by several different variables, all of which are part of the steps in the procedure, and by the characteristics of the screened population. Abstract : The determinants of adequacy and positivity of the p16/Ki‐67 assay are described in a human papillomavirus‐positive screening population. Even using the same assay and reporting the results according to the same criteria, the findings suggest that many variables linked to the characteristics of the population under study, the laboratory that performs the immunostaining, and/or the laboratory that interprets the slides should be taken into consideration.